HUBUNGAN KEPEMIMPINAN DEMOKRATIS DENGAN LOYALITAS KERJA KARYAWAN PARAMEDIS RUMAH SAKIT NUSA LIMA PEKANBARU - Vika Riyanti; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Nusa Lima Hospital is one of hospital in Pekanbaru, which engaged health care services. It is a hospital that built by PT. Perkebunan Nusatara Lima. It has purpose to assist and improve the achievement for corporate’s goals. The others function of this hospital are forhealth care employees and their families, and the other patients too.The purpose of this study is for analyze the relationship between the achievement assessments and employee performance. This study uses quantitative descriptive method with correlationak techniques. In which the data was collected by questioners method for was us respondent. After that, it was done by using spearman analysis for the data that been gottenThe result of this study and hypothesis testing showed hat there is a significant positive relationship between democratic leadershipand employees loyalty working in Nusa Lima hospital Pekanbaru. Through correlation analysis by Spearman Rank know that the assessmen of leadership and working loyalty have coefficient value. It is 0,647, here coefficient interpretation correlation valu to identify the relationship between democratic leadership employee’s loyalty is strong categorized.Key words : Democratic Leadership, Loyalty Working, Hospital.